Probiotic properties of lactic acid bacteria obtained from intensive snakehead fish (Channa striata) culture ponds - NGUYEN TRI YEN CHI; NGUYEN LU KHOI MINH; QUACH VAN CAO THI (Society for Indonesian Biodiversity, 2025)
Abstract. Chi NTY, Minh NLK, Thi QVC. 2025. Probiotic properties of lactic acid bacteria obtained from intensive snakehead fish (Channa striata) culture ponds. Biodiversitas 26: 1171-1179. Intensively farmed snakehead fish (Channa striata, hereinafter referred to as C. striata) in Vinh Long Province of the Mekong Delta, Vietnam, have suffered significant harm from Aeromonas schubertii (hereinafter can be written as A. schubertii), the causative agent of visceral white spot disease. Hence, the purpose of the present study was to collect and select Lactic Acid Bacteria (LAB) with potential probiotic properties. The finding revealed that twenty-three LAB strains were yielded from pond water samples and fish guts. Regarding probiotic features, eleven of twenty-three LAB strains exhibited antagonistic activity against A. schubertii. Among them, strain LABB, which displayed the highest antibacterial activity, was classified as Lactiplantibacillus based on morphological, physiological, biochemical, and phylogenetic analysis results in the investigation. After 24 hours of incubation, strain LABB was able to survive in media with a pH between 2.0 and 4.0. Strain LABB, in particular, showed the ability to withstand bile salt at contents of 0.3% and 0.5% after being inoculated for 24 and 3 hours, respectively. Besides, the findings also revealed that the strain LABB could produce extracellular enzymes such as protease, amylase, and cellulase. Additionally, this bacterial strain was susceptible to penicillin, levofloxacin, ofloxacin, erythromycin, clindamycin, doxycycline, ampicillin, ampicillin/sulbactam, and chloramphenicol. According to research findings, LABB may be used to manage A. schubertii, which causes visceral white spot disease in farmed snakehead fish.